Optimal Control in Autonomous Driving. Issue 1 (15th March 2018) - Cobus, Andreas; Rick, Matthias; Sommer, Laura; Backfisch, Niels; Probst, Alexander; Echim, Mitja; Büskens, Christof
Abstract: Autonomous driving is no longer a subject of science fiction. Instead it has become a field of highly topical developments and has already reached numerous milestones. The Audi Autonomous Driving Cup provides a stage for students to participate in this development process. This competition, carried out in Germany, Austria and Switzerland, provides miniature vehicles of normed hardware to the participants which have the task of implementing algorithms for autonomous handling of problems such as lane tracking, obstacle detection, adaptive cruise control, overtaking, turning as well as entering and exiting parking spaces. To present the concept of optimal control based on a single track model in combination with image processing methods we focus in this paper on the parking manoeuvre only. Thereby we show that optimization and control techniques can play a key role in the design of autonomous vehicles. (© 2017 Wiley‐VCH Verlag GmbH & Co. KGaA, Weinheim)